Regional Astrogeodetic Validation of GPS/Levelling Data and Quasigeoid Models - Voigt, C.; Denker, H.; Hirt, Christian (Springer, 2007)
In the context of a GOCE regional validation and combination experiment in Germany, a work package within the framework of the GOCE-GRAND II project, gravity observations, vertical deflections and GPS/levelling data are collected as independent data sets. The observation of absolute gravity values is carried out by the Bundesamt fr Kartographie und Geodsie (BKG), while the vertical deflections are observed by the Institut fr Erdmessung (IfE) using the Hannover digital transportable zenith camera system TZK2-D. The vertical deflections have an accuracy of approx. 0.1 arc seconds and are arranged along a North-South and East-West profile. The two profiles have a length of about 500 km each with a spacing of 2.5-5 km between adjacent stations. Furthermore, a national GPS and levelling data set of about 900 stations with an accuracy of approx. 1 cm is available for Germany. The analysis of the vertical deflections is carried out by the astronomical levelling method, resulting in two (quasi)geoid profiles. The accuracy of the profiles is expected to be at the cm level. A cross-validation of both the vertical deflection and GPS/levelling data is realised by traversing the profiles through all nearby GPS/levelling stations (approx. 40 in total). In addition, comparisons are performed with the German Combined QuasiGeoid 2005 (GCG05) and the purely gravimetric solution EGG07 (European Gravimetric Quasigeoid 2007)